By the method of Euler-Cauchy , we have to solve this differential equation -
"=(x^{4}D^{4}+6x^{3}D^{3}+9x^{2}D^{2}+3xD+1)y=(1+lnx)^{2}"
Now let , "x=e^{t}" , Taking log both the side of given equation , we get ,
"=lnx=t"
Now we know that "," the terms on left hand side of given differential equation can be reduces into linear differential equation , by putting the formulas -
"=x^{4}D^{4}=D(D-1)(D-2)(D-3)y"
"=x^{3}D^{3}=" "D(D-1)(D-2)y"
"=x^{2}D^{2}=D(D-1)y"
"=xD=Dy"
Putting all these above values in the given equations , we get -
"=" "(D(D-1)(D-2)(D-3)+6D(D-1)(D-2)+9D(D-1)+3D+1)y=(1+t)^{2}"
Now , solving we get as -
"=" "(D^{4}+2D^{2}+1)y=(1+t)^{2}"
It's Auxiliary equation will be -
"=m^{4}+2m^{2}+1=0"
"=m^{4}+m^{2}+m^{2}+1=0"
"=m^{2}(m^{2}+1)+1(m^{2}+1)=0"
"=(m^{2}+1)^{2}=0"
"m={\\pm}i"
so "CF=[(c_1+c_2x)cosx+(c_3+c_4x)sinx]"
Now to find "PI" of given function , we get -
"PI=\\dfrac{1}{D^{4}+2D^{2}+1}" "(1+t)^{2}"
"PI=(1+D^{4}+2D^{2})^{-1}(1+t)^{2}"
Now using Binomial expansion of "(1+x)^{-1}=1-x+x^{2}+...."
Now applying this series in above equation we get ,
"PI=(1-D^{4}-2D^{2})(1+2t+t^{2})"
"PI=1+2t+t^{2}-4=t^{2}+2t-3"
Solution of given Partial differential equation can be written as -
"Y=CF+PI=" "[(c_1+c_2x)cosx+(c_3+c_4x)sinx]+(lnx)^{2}+2lnx-3"
which is required solution of given partial differential equation .
Comments
Leave a comment